MiR-199a-3p downregulation in thyroid tissues is associated with invasion and metastasis of papillary thyroid carcinoma. Issue 2 (3rd April 2017) - Liu, Chengbiao; Xing, Meiling; Wang, Liping; Zhang, Kejun
Abstract: Background and aims: miR-199a-3p may play an important role in tumour inhibition. The aim of the present study was to determine any link between miR-199a-3p expression in thyroid tissues and clinicopathologic features, as well as to assess potential usefulness of miR-199a-3p in prediction for invasion and metastasis of papillary thyroid carcinoma (PTC). Methods: A total of 188 tissue samples (136 PTCs, 52 normal thyroid tissue) were collected. We measured the levels of miR-199a-3p with quantitative reverse-transcriptase PCR (RT-qPCR) in all subjects. In addition, the correlation between the expression levels of miR-199a-3p and clinicopathological factors was explored. Results: qRT-PCR indicated that the expression levels of miR-199a-3p was 7.1 (95% CI, 3.9–12.4) in PTCs, which was significantly lower than that of in the normal thyroid tissues 31.4 (95% CI, 15.4–44.3) ( p = 0.002). Receiver operating characteristic curve (ROC) analyses revealed that miR-199a-3p could be promising biomarkers for PTC, with relatively high area under the curve (AUC) values was 0.87 (95% CI, 0.66–0.90; p = 0.001). Low miR-199a-3p expression levels were linked to TNM stage ( p = 0.026), extra-thyroidal extension ( p = 0.02), lymph node (LN) metastasis ( p = 0.036), distant metastasis ( p = 0.002) and recurrence of LN metastasis ( p = 0.03). Conclusions: Our data suggest that downregulation of miR-199a-3p in thyroid tissues is linked to invasion and metastasis of PTC and may be a potential target for therapeutic intervention.